1999
DOI: 10.1128/jcm.37.12.4145-4149.1999
|View full text |Cite
|
Sign up to set email alerts
|

Unusual, High Genetic Diversity of Aleutian Mink Disease Virus

Abstract: The genetic diversity of Aleutian mink disease virus (AMDV) was examined. Sequences obtained from 35 clinical samples were compared with five published sequences. An unusual, high genetic variability was revealed. Three phylogenetic subgroups of AMDV were identified, and the presence of more than one genotype at some farms was detected.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
36
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 14 publications
4
36
0
Order By: Relevance
“…As in previous analyses, no clustering of AMDV isolates according to pathogenicity was detected, indicating that highly pathogenic strains may appear spontaneously from different genetic origins (Knuuttila et al. 2009; Olofsson et al. 1999), although the sequencing of larger segments of the virus may elucidate sites more critical for virulence.…”
Section: Discussionmentioning
confidence: 47%
See 2 more Smart Citations
“…As in previous analyses, no clustering of AMDV isolates according to pathogenicity was detected, indicating that highly pathogenic strains may appear spontaneously from different genetic origins (Knuuttila et al. 2009; Olofsson et al. 1999), although the sequencing of larger segments of the virus may elucidate sites more critical for virulence.…”
Section: Discussionmentioning
confidence: 47%
“…We amplified nucleotide fragments of the hypervariable regions of both the AMDV NS1 and VP2 genes from the isolated DNA by polymerase chain reaction (PCR) using previously described primers (Oie et al. 1996; Olofsson et al. 1999).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Identical ADV strains detected in both farmed mink and vicinal raccoons in Utah experimentally caused disease in mink but not raccoons (Oie et al., ). Molecular studies on ADV isolated from farmed mink demonstrated three subgroups with high genetic diversity of strains and differing degrees of pathogenicity in each subgroup (Olofsson et al., ). Multistrain infections on mink farms were common, presenting a further challenge to correlation of disease severity with a specific viral strain (Olofsson et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…Molecular studies on ADV isolated from farmed mink demonstrated three subgroups with high genetic diversity of strains and differing degrees of pathogenicity in each subgroup (Olofsson et al., ). Multistrain infections on mink farms were common, presenting a further challenge to correlation of disease severity with a specific viral strain (Olofsson et al., ). Further molecular characterization is needed to determine whether pathogenic and non‐pathogenic genotypes of ADV exist within the BC skunk reservoir.…”
Section: Discussionmentioning
confidence: 99%